MILLENNIAL’S RATIONAL DECISION CHOICE TO BECOME FARMERS IN TERMS OF ECONOMIC’S CHARACTERISTIC IN SUKOHARJO - Indah Susilowati; Siti Nur Arofah; Muhammad Fahrur Rozi; Hira Davika (Asosiasi Dosen Muda Indonesia, 2024)
The purpose of this research is to identify the factors that influence the interest of the younger generation in working in the rice farming sector in Polokarto District, Sukoharjo Regency. The method used in this research is the binary logistic regression model, which is a logistic regression with two categories or binomial on its dependent variable. The data in this study were obtained from primary and secondary data. Secondary data were obtained from relevant agencies or government institutions, including data on the number of labor forces and rice farmers in 2022 in Polokarto District. Primary data were obtained directly from the labor force working in the rice agriculture sector in Polokarto District. Descriptive analysis through observation techniques, in-depth interviews (wawancara mendalam). The population in this study was conducted in the Polokarto District with specific criteria. And the sample consists of 100 rice farmers and non-farmers aged (15-39 years) with a distribution of 20 farmers from each of the five villages (Polokarto, Karangwuni, Wonorejo, Kenokorejo, Bakalan) in the Polokarto District. The results of this study indicate that the variables of Wages, Land Area, and Gender partially have a positive and significant effect on the interest of the younger generation to work in the agricultural sector. The number of dependents has a negative and significant effect, while education does not have an effect on the interest of the younger generation to work in the agricultural sector.